Clinicopathological and prognostic analyses of 86 resected pulmonary lymphoepithelioma‐like carcinomas. Issue 2 (30th October 2020) - Chen, Jiafei; Gu, Chang; Chen, Xiaojian; Dai, Chenyang; Zhao, Shengnan; Xie, Huikang; Fei, Ke; Chen, Chang
Abstract: Background: Pulmonary lymphoepithelioma‐like carcinoma (LELC) is a rare subtype of primary lung cancer. The present study aims at investigating clinicopathological features and prognostic characteristics of the resected pulmonary LELC. Methods: Patients with resected pulmonary LELC were identified in our hospital from December 2008 to December 2018. Data of these patients were retrospectively reviewed, clinicopathological features and prognostic characteristics were analyzed subsequently. Results: In total, 86 patients were enrolled in the study, including 39 (45.3%) males and 47 (54.7%) females. Most of the serum tumor markers were normal. Immunohistochemical staining result showed frequent differentiation traits of epithelial tissue such. Positive PD‐L1 (15 of 19, 78.9%) and PD‐1 (13 of 17, 76.5%) were also common, but cancer‐related genetic mutation was scarce (1 of 47, 2.1%). Survival analyses demonstrated that the N stage ( p = .011) and extent of resection ( p = .023) were identified as independent predictive factors for overall survival. Conclusions: Pulmonary LELC is a distinctive subtype of lung cancer with several exclusive traits, such as the trend to happen among nonsmoking young people, epithelial origin of tumor differentiation, frequent expression of the immune checkpoint, and scarce presence of driver mutation. In addition, pulmonary LELC was apt to get a favorable outcome, especially in cases diagnosed and treated in the early stage.